Hypogalactosylation of immunoglobulin G (IgG) of gingival fluid and saliva at the patient with periodontal disease - Stefanović Gordana; Ćirić Dragana; Ilić Vesna; Brajović Gavrilo; Petrović Sonja; Milošević Dragan; Milošević-Jovčić Nadežda (Serbian Medical Society - Dental Section, Belgrade, 2006)
Changed glycosylation of immunoglobulin G (IgG), above all, the expression of thermal galactose, influence to numerous functions of those immunoglobulin and correlate with the inflammatory level in a number of diseases. Aim: This work analyses the distribution of IgG subclasses and the content of thermal galactose in them, in saliva and gingival fluid of the patients with periodontal disease and different gum inflammatory level. Materials and methods: It was used saliva and gingival fluid of 30 adults with clinical picture of periodontal disease and 20 persons with healthy periodontium. The qualification of IgG was done by "dot-blot" procedure and the, and thermal galactose was determined by lectin immunoblot procedure. Results: The division of IgG subclasses in both fluids was different in the patients with periodontal disease and in control samples. In saliva and gingival fluid of the diseased quantitatively dominated IgG2 subclasses, independently from periodontal status. In IgG of both fluids, thermal galactose was exprimated at the healthy periodontium persons (control) and with the person with initial periodontal disease, while at the person with increased periodontal disease the expression of this saccharide wasn't registered in neither of fluids. Conclusion: The results showed that there is a shift towards hypogalactosyled IgG glikoforms during the process of gum inflammation at the periodontal disease patients. .